Factors associated with late presentation for HIV/AIDS care in Harare City, Zimbabwe, 2015. (December 2016) - Nyika, Howard; Mugurungi, Owen; Shambira, Gerald; Gombe, Notion; Bangure, Donewell; Mungati, More; Tshimanga, Mufuta
Abstract Background Despite widespread awareness and publicity concerning Human Immunodeficiency Virus (HIV) care and advances in treatment, many patients still present late in their HIV disease. Preliminary review of the Antiretroviral Therapy (ART) registers at Wilkins and Beatrice Road Hospitals, both located in Harare, indicated that 67 and 71 % of patients enrolled into HIV/AIDS care presented late with baseline CD4 of <200 cells/uL and/or WHO stage 3 and 4 respectively. We therefore sought to explore factors associated with late presentation in Harare City. Methods We conducted a 1:1 unmatched case control study where a case was an HIV positive individual (>18 years) with a baseline CD4 of <200/uL or who had WHO clinical stage 3 or 4 at first presentation to OI/ART centres in 2014 and; a control was HIV positive individual (>18 years) who had a baseline CD4 of >200/uL or WHO clinical stage 1 or 2 at first presentation in 2014. Written informed consent was obtained from all study participants. Results A total of 268 participants were recruited (134 cases and 134 controls). Independent risk factors for late presentation for HIV/AIDS care were illness being reason for test (Adjusted Odds Ratio [aOR] =7.68, 95 % CI = 4.08, 14.75); Being male (aOR = 2.84, 95 % CI = 1.50, 5.40) and; experienced HIV stigma (aOR = 2.99, 95 % CI = 1.54, 5.79). Independent protective factors were receiving information on HIV (aOR = 0.37, 95 % CI = 0.18, 0.78) and earning more than US$250 per month (aOR = 0.32, 95 % CI = 0.76, 0.67). Median duration between first reported HIV positive test result and enrolment into pre-ART care was 2 days (Q1  = 1 day; Q3  = 30 days) among cases and 30 days (Q1  = 3 days; Q3  = 75 days) among controls. Conclusion Late presentation for HIV/AIDS care in Harare City was a result of factors that relate to the patient's sex, reason for getting a test, receiving HIV related information, experiencing stigma and monthly income. Based on this evidence we recommended targeted interventions to optimize early access to testing and enrolment into care.